STRATEGI KOMUNIKASI PEMASARAN PADA KOPI OGUT KAFÉ DALAM MENARIK MINAT KONSUMEN - Eko Purwanto; Selly Oktarina; Abdul Basit; Mirza Shahreza; Anna Gustina Zainal; Ana Kuswanti; Lusiana Setianti (Communication Science Department at Universitas Lampung, 2022)
This study focuses on how the marketing communication strategy for Café Ogut Cofee in attracting consumers' interest and the factors influence the marketing communication strategy for Café Ogut Cofee in attracting consumers' interest. The method used in this study is a qualitative research method using interview, observation and documentation techniques as data collection. After conducting research, it was found that the marketing communication strategy applied by Café Ogut Cofee uses the concept of the marketing mix that he uses including, produst, place, price, promotion, people, physical evidence, and process. Of the seven elements, Café Ogut Cofee uses all elements of the marketing mix including product, place, price, promotion, physical evidence and process. The driving factors that influence the marketing communication strategy of Café Ogut Cofee are the existence of board game facilities for visitors so that it becomes an attraction for Café Ogut Cofee and the inhibiting factor is the lack of space or place for events such as live music to reduce the attractiveness of Café Ogut Cofee and become obstacle to the smooth marketing mix of Café Ogut Cofee.